The Marvels [videorecording (DVD)] - DaCosta, Nia, 1989-; McDonnell, Megan; Karasik, Elissa; Larson, Brie, 1989-; Parris, Teyonah; Vellani, Iman; Ashton, Zawe; Lewis, Gary, 1958-; Pak, Sŏ-jun, 1988-; Shroff, Zenobia (Actor); Kapur, Mohan; Shaikh, Saagar; et al. (Marvel Studios, 2024)
Carol Danvers gets her powers entwined with those of Kamala Khan and Monica Rambeau, forcing them to work together to save the universe.